Kebijakan Hukum Pidana mengenai Kejahatan Judi Online (Cyber Gambling) di Indonesia - Firmansyah Firmansyah (Pusat Riset dan Inovasi Nasional, 2025)
The development of information technology has made it easier for people to access various digital services, including online gambling or cyber gambling, which has now become a global phenomenon and has given rise to various legal problems. In Indonesia, online gambling crimes are increasingly widespread and disturbing, considering the negative impact on society, especially in the economic, social and mental aspects of society. Criminal law policy in Indonesia, especially in handling online gambling crimes, still faces a number of challenges, both in terms of statutory regulations and the implementation of effective law enforcement. This research aims to examine criminal law policies in Indonesia in dealing with online gambling crimes, analysis of the challenges faced in law enforcement, and recommendations needed to strengthen efforts to eradicate this crime. Using a normative juridical approach, the research results show that although there are provisions in the Criminal Code and related laws that regulate gambling, existing regulations are still unable to fully address the complexity and dynamics of online gambling crimes. Therefore, more comprehensive legal policy steps are needed, including updating regulations and increasing the capacity of law enforcement in eradicating online gambling in Indonesia.